Towards the enlightenment through the deadness : urban renewal in Motijheel commercial area of Dhaka city Motijheel, Dhaka - Al Mahmud, Mohammed Abdullah (BRAC University, 2018)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Architecture, 2017.